Management control systems in Madeira island largest firms: Evidence on the balanced scorecard usage - Carla Curado; José Manica (Journal of Business Economics and Management, 2010)
This paper describes the findings of an exploratory study on the use of management control systems in Madeira Island providing evidence on the Balanced Scorecard (BSC) usage. Empirical data collected illustrates the degree of BSC usage at the Island's biggest corporations and provides response to the research questions. The findings reveal remarkable differences concerning management control systems’ use across corporations in the study and previous research reports from other regions. Finally, this study discusses managerial implications and includes invitations to future research directions.